Peran Guru Bimbingan dan Konseling dalam Pelaksanaan Kegiatan Kunjungan Rumah pada SMP Negeri di Kota Padang - Aziza, Hestyana; Yusuf, A. Muri; Sukmawati, Indah (Konselor, 2013)
Teacher Guidance and Counseling (BK) has a role in the implementation of home visits aimed to obtain and collect data. The reality is less BK teacher roles in the implementation of home visits, teachers held a BK less preparation in determining the timetable for implementation, BK teachers do home visits rarely communicate to students, with the teacher's role in the implementation of activities BK home visits has not done well. This research is a descriptive study, with a sample based on random cluster sampling, the number of teachers BK 20 people. The results: (1). BK teacher's role in communicating the plan home visits to related parties are on both criteria. (2). BK teacher's role in carrying out home visits on both criteria. BK teacher's role in carrying out home visits on both criteria. Based on the research findings, the role of teachers in the implementation of BK kunjuungan home located on both criteria. Keywords: BK teacher's role, activities home visits.